PENGGUNAAN BEASISWA BIDIKMISI PADA MAHASISWA MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PAPUA - Ramadhoni, Afif; Usman, Sarah; Suruan, Ted Matheus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The Bidikmisi Scholarship is tuition assistance given to students who are economically disadvantaged and have good academic potential, namely having a good Grade Point Average (GPA) determined by the university. The purpose of this research is to find out how much is the allocation of Bidikmisi scholarship by management students of Bidikmisi scholarship recipients for educational needs, living expenses and temporary living expenses. This type of research approach is quantitative research, with descriptive problems. The sample is 44 students majoring in management, Faculty of Economics and Business, University of Papua. Data were collected using an online questionnaire. Descriptive statistical analysis tools are frequency and percentage. The use of Bidikmisi scholarships for students of the Management Department of FEB, University of Papua, is an average of 30% (13 people) out of a total of 44 students who spend IDR 4,400,000 for educational needs. as much as 26.7% spent Rp1,150,000 for the necessities of life. According to 68.2% of students, student aid funds from outside the province, the highest aid was Rp. 3,000,000 answered by 4.5% of students. There are advantages to using students, they should be used for the personal needs of Bidikmisi recipients. It includes consumption, transportation, credit and other costs that can ease the burden on parents.